Stress responsiveness of the hypothalamic-pituitary-adrenal axis: age-related features of the vasopressinergic regulation - Goncharova, Nadezhda D. (Frontiers in Endocrinology, 2013)
The hypothalamic-pituitary-adrenal (HPA) axis plays a key role in adaptation to environmental stresses. Parvicellular neurons of the hypothalamic paraventricular nucleus secrete corticotrophin releasing hormone (CRH) and arginine vasopressin (AVP) into pituitary portal system; CRH and AVP stimulate ACTH release through specific G protein-coupled membrane receptors on pituitary corticotrophs, CRH1 for CRH and V1b for AVP; the adrenal gland cortex secretes glucocorticoids in response ACTH. The glucocorticoids activate specific receptors in brain and peripheral tissues thereby triggering the necessary metabolic, immune, neuromodulatory and behavioral changes to resist stress. While importance of CRH, as a key hypothalamic factor of HPA axis regulation in basal and stress conditions in most species, is generally recognized, role of AVP remains to be clarified. This review focuses on the role of AVP in the regulation of stress responsiveness of the HPA axis with emphasis on the effects of aging on vasopressinergic regulation of HPA axis stress responsiveness. Under most of the known stressors, AVP is necessary for acute ACTH secretion but in a context-specific manner. The current data on the AVP role in regulation of HPA responsiveness to chronic stress in adulthood are rather contradictory. The importance of the vasopressinergic regulation of the HPA stress responsiveness is greatest during fetal development, in neonatal period, and in the lactating adult. Aging associated with increased variability in several parameters of HPA function including basal state, responsiveness to stressors, and special testing. Reports on the possible role of the AVP/V1b receptor system in the increase of HPA axis hyperactivity with aging are contradictory and requires further research. Many contradictory results may be due to age and species differences in the HPA function of rodents and primates.